Identifcation of antibiotic producing endophytic microbe isolates from a national park in Java island - Sri Yuwantiningsih; Sebastian Margino; Subagus Wahyuono (Indonesian Journal of Biotechnology, 2015)
Endophytic microbes are potential sources of antibiotics. Some numbers of endophytic bacteria were isolated from plants in Ujung Kulon, Kaliurang, Meru Betiri and Baluran National Park, Bogor Botanical Garden, and Nusakambangan forest, Indonesia. Previous studies have been conducted to examine and obtain endophytic bacteria isolates from the selected plants, which resulted in three selected isolates, namely OOH-1, STG-1, and CMB-2. This research was conducted to determine the molecular identity of OOH-1 and STG-1 isolates, as well as to identify antibiotic compounds produced by STG-1 isolate. Molecular identifcation of selected isolates was based on 16S rRNA gene analysis and amplifed using primers 27F and 1492R. A phylogeny tree was then constructed by comparing the resulting sequences with data from Gene Bank using the BLAST-N program. The identifcation showed that STG-1 isolate had a 99% similarity with Pseudomonas brenneri strain SFML 97-391, and OOH-1 isolate had a 99% similarity with Enterobacter xiangfangensis. Identifcation of antibiotic compounds was done by purifcation and separation of the compounds. Antibiotic activity was also examined based on Lethal Concentration (LC50) on Fusarium oxysporum with a LC50 of 0.01–0.02% against Fusarium oxysporum.